Architecture students’ conceptions, experiences, perceptions, and feelings of learning technology use: Phenomenography as an assessment tool - Ebenezer, Jazlin; Sitthiworachart, Jirarat; Na, Kew Si (My University, 2022)
The primary purpose of this phenomenographic qualitative study is to identify a group of second-year undergraduate architecture students’ conceptions of learning technology use. The secondary purpose is to examine students’ learning experiences, perceptions, and feelings of technology use in an education course. Data were collected over a week by individually interviewing 15 architecture students, who were becoming teachers of architecture. Each 20-min individual interview was audio-recorded, transcribed verbatim, translated into English, and analysed to identify descriptive categories of the students’ conceptions of learning technology use. The six descriptive categories were: learning online; searching for information and knowledge, defining social media connectivity, exploring a virtual place, designing a model house, and transferring knowledge and understanding. Most architecture students expressed the technology-integrated lessons were interesting. The architecture students perceived educational games as the most useful teaching tools in their future classrooms. The study implies phenomenography can be used as an assessment tool to identify students’ conceptions and characterize their structural aspects, which may be used as curriculum frameworks to design content that moves architecture students from the periphery to the core of the subject.
Keywords: Architecture students; Higher education; Learning technology; Phenomenography